2019
DOI: 10.1155/2019/7825915
|View full text |Cite
|
Sign up to set email alerts
|

Case of Cardiac Arrest Treated with Extra-Corporeal Life Support after MDMA Intoxication

Abstract: Objective. To describe the case of a patient who developed a serotonin syndrome due to a 3,4-methylenedioxymethamphetamine ingestion with electrical storm and refractory cardiac arrest. Design. Case report. Study Selection. ICU of a university hospital. Patient. A 22-year-old man transferred to the emergency room with hyperthermia, tremors, and mydriasis presented a cardiac arrest due to ventricular fibrillation. Interventions. We implemented extra-corporeal life support combined with vasoactive drugs. Later, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…104 MDMA has been reported to provoke SCD in patients with channelopathies 98 and electrical storm as a result of serotonin syndrome. 105 Prescription amphetamine use has not been associated with SCD in children 106 and adults. 107 In a study involving 100 autopsies 108 of individuals testing positive for methamphetamine, moderate-to-severe atherosclerosis was found in only 17%.…”
Section: Substituted Amphetamines and Sudden Arrhythmic Deathsmentioning
confidence: 98%
See 2 more Smart Citations
“…104 MDMA has been reported to provoke SCD in patients with channelopathies 98 and electrical storm as a result of serotonin syndrome. 105 Prescription amphetamine use has not been associated with SCD in children 106 and adults. 107 In a study involving 100 autopsies 108 of individuals testing positive for methamphetamine, moderate-to-severe atherosclerosis was found in only 17%.…”
Section: Substituted Amphetamines and Sudden Arrhythmic Deathsmentioning
confidence: 98%
“…Electrical storms due to MDMA-induced serotonin syndrome can be treated by treating hyperthermia, managing autonomic instability, and serotonin antagonism. 105 Extracorporeal life support has been previously used for recurrent and refractory electrical storms caused by substituted amphetamines. 105…”
Section: Treatment Of Arrhythmias In Patients With Substituted Amphet...mentioning
confidence: 99%
See 1 more Smart Citation
“…These differences are not addressed by current resuscitation guidelines. Although overall outcomes are poor, neurologically intact survival has been reported, even where temperatures historically regarded as fatal are encountered 4 . Existing evidence regarding the epidemiology and management of out-of-hospital cardiac arrest associated with intra-arrest hyperthermia is largely confined to case reports focused almost exclusively on heat illness and drug-related presentations.…”
Section: Introductionmentioning
confidence: 99%
“…Excessive serotonin release and consequent overactivation of central and peripheral serotonin receptors are known to cause serotonin syndrome [14]. For instance, abuse of serotonergic compounds, such as methylenedioxymethamphetamine (MDMA) [17][18][19][20][21][22], 5-methoxy-N,N-dimethyltryptamine (5-MeO-DMT) [23], and psilocybin [24], or dissociative drugs, such as dextromethorphan [25][26][27][28], has been reported to provoke serotonin syndrome in humans. Indeed, it has been reported that frequent usage of antidepressants, such as monoamine oxidase (MAO) inhibitors and selective serotonin reuptake inhibitors (SSRIs), enhances the risk of serotonin syndrome [14,29].…”
Section: Introductionmentioning
confidence: 99%